DEVELOPING AWARENESS OF JAMA’AH PRAYER AT THE BABUL ULUM ISLAMIC BOARDING SCHOOL LUNG IE VILLAGE KRUENG BARONA JAYA SUB DISTRICT ACEH BESAR DISTRICT - Murni, Murni; Suzanni, Suzanni; Aklima, Siti (PT. Antis International Publisher, 2024)
Jama’ah prayer is one of the important practices in Islam which has many advantages, including building spiritual awareness, discipline, and strengthening social ties among Muslims. At the Babul Ulum Islamic Boarding School, Lung Ie Village, Krueng Barona Jaya Sub District Aceh Besar Districk, jama’ah prayer is an integral part of the religious education applied to students. Fostering awareness of jama’ah prayer is carried out through various methods, such as direct teaching, strict supervision from the ustadz, examples from the instructors, and routine habits in the daily activities of the students. This research method uses a qualitative approach with a field research type. The results of the study indicate that 1). The process of fostering awareness of jama’ah prayer implemented at the Babul Ulum Islamic Boarding School, Lung Ie Village, Krueng Barona Jaya Sub District Aceh Besar Districk has been running well and has had a positive impact on the discipline and spirituality of students, although ongoing efforts are still needed to strengthen the internal awareness and spiritual independence of students. 2). The main supporting factors in fostering awareness of jama’ah prayer at the Babul Ulum Islamic Boarding School Lung Ie Village Krueng Barona Jaya Sub District Aceh Besar Districk are the commitment of the ustadz, the Islamic environment, and a structured coaching system. However, inhibiting factors such as differences in students' internal motivation, habits that are difficult to instill, and the influence of gadgets need more attention. To overcome these obstacles, Islamic boarding schools need to continue to improve their more personal approach, strict supervision, and strengthening spiritual awareness through ongoing coaching.